Food environment and childhood obesity: The effect of dollar stores - Andreas C. Drichoutis; Rodolfo M. Nayga; Heather L. Rouse; Michael R. Thomsen (Health Economics Review, 2015)
In this paper we examine the effect of dollar stores on children's Body Mass Index (BMI). We use a dataset compiled by the Arkansas Center for Health Improvement that reflects a BMI screening program for public school children in the state of Arkansas. We combine propensity score matching with difference-in-differences methods to deal with time-invariant as well time-varying unobserved factors. We find no evidence that the presence of dollar stores within a reasonably close proximity of the child's residence increases BMI. In fact, we see an increase in BMI when dollar stores leave a child's neighborhood. Given the proliferation of dollar stores in rural and low-income urban areas, the question of whether dollar stores are contributing to high rates of childhood obesity is policy relevant. However, our results provide some evidence that exposure to dollar stores is not a causal factor.
Keywords: D10; I10; C31; C33; R10; 330; Childhood obesity; Food-at-home; Propensity score matching; Difference-in-differences